2015
DOI: 10.1016/j.jpor.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dry mouth: A critical topic for older adult patients

Abstract: It is important to understand the causes of dry mouth and to educate our patients. Starting a prevention program as early as possible considering the most practical, cost effective and efficient treatments with the best risk-benefit ratio will help to diminish dry mouth symptoms and sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
147
0
77

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(231 citation statements)
references
References 83 publications
7
147
0
77
Order By: Relevance
“…31 Several studies have reported xerostomia to be more frequently related with older age, especially in populations over 60 years of age. 2,26 The explanation may be that age acts as a risk factor, or it could be that elderly patients have more risk factors than younger people. Older age is associated with more chronic diseases, which is associated with more drug intake, and this is the most common cause of dry mouth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Several studies have reported xerostomia to be more frequently related with older age, especially in populations over 60 years of age. 2,26 The explanation may be that age acts as a risk factor, or it could be that elderly patients have more risk factors than younger people. Older age is associated with more chronic diseases, which is associated with more drug intake, and this is the most common cause of dry mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al reported a 33.5% prevalence of xerostomia in patients with a daily intake of at least three drugs, and a 67% prevalence in patients who take more than seven drugs a day. 2 Yuan et al found an increase in the prevalence of dry mouth when patients took more than three medications. 32 Field et al 12 concluded that medication is a highly significant risk factor for having a dry mouth, and is a better predictor of risk status than either age or gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a clear work overload among women, which may have an influence on their health condition. According to the World Health Organization, several health problems experienced by older women result from risk factors to which they are exposed during their life 8 . On that note, it is important to observe that risk factor commonly linked to males, such as alcohol or tobacco consumption, have been gradually changing over the year, and are link to other cultural and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dry mouth syndrome is a risk factor for oral diseases, including microbial infections, such as dental caries, periodontitis, and candidiasis [1]. Decreased saliva secretion occurs as a symptom of disease, such as diabetes, or as an adverse effect of drug administration [2].…”
Section: Introductionmentioning
confidence: 99%